Perbandingan Algoritma Random Forest, Naïve Bayes, dan Support Vector Machine Pada Analisis Sentimen Twitter Mengenai Opini Masyarakat Terhadap Penghapusan Tenaga Honorer - Akhmad Miftahusalam; Adinda Febby Nuraini; Awalia Agustina Khoirunisa; Hasih Pratiwi (Seminar Nasional Official Statistics, 2022)
Employees are an important asset in agencies, who plan and act for every activity of an organization, as well as in government agencies. Although employees are important in government agencies, it is not easy to get employees due to the difficulty of approval from the Ministry of State Apparatus Utilization and Bureaucratic Reform. This is what triggers the emergence of temporary or contract workers. The goal is to meet the needs of vacant employees. However, after serving for decades, the government announced it would eliminate the appointment of temporary employees. This news certainly raises the pros and cons in society. To see people's opinion on this issue, the Twitter platform can be used as a data source. Many users are actively writing information in the form of tweets related to the removal of temporary workers. There were 2690 tweets in a week that discussed honorary workers. With the Random Forest method, an accuracy of 66,67% is obtained.